2002
DOI: 10.1038/nn817
|View full text |Cite
|
Sign up to set email alerts
|

Reorganization of human cortical maps caused by inherited photoreceptor abnormalities

Abstract: We describe a compelling demonstration of large-scale developmental reorganization in the human visual pathways. The developmental reorganization was observed in rod monochromats, a rare group of congenitally colorblind individuals who virtually lack cone photoreceptor function. Normal controls had a cortical region, spanning several square centimeters, that responded to signals initiated in the all-cone foveola but was inactive under rod viewing conditions; in rod monochromats this cortical region responded p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
159
2
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 155 publications
(175 citation statements)
references
References 28 publications
4
159
2
2
Order By: Relevance
“…It is important to note that none of these studies can measure the same neuron at multiple time points, but rather, they must sample from active neurons in similar locations, resulting in potential sampling biases that further complicate their interpretations (2,27). Similar conflicting measurements have been seen in human patients with bilateral foveal lesions from age-related macular degeneration, with some fMRI studies claiming extensive recovery within the V1 SPZ, whereas again, others showed no evidence for reorganization (7,18,35,(43)(44)(45).…”
Section: Comparisons With Studies On the Cortical Effects Of Other Rementioning
confidence: 98%
See 3 more Smart Citations
“…It is important to note that none of these studies can measure the same neuron at multiple time points, but rather, they must sample from active neurons in similar locations, resulting in potential sampling biases that further complicate their interpretations (2,27). Similar conflicting measurements have been seen in human patients with bilateral foveal lesions from age-related macular degeneration, with some fMRI studies claiming extensive recovery within the V1 SPZ, whereas again, others showed no evidence for reorganization (7,18,35,(43)(44)(45).…”
Section: Comparisons With Studies On the Cortical Effects Of Other Rementioning
confidence: 98%
“…Third, the scotoma arises because of the central fovea's complete lack and surrounding paucity of rod photoreceptors, allowing for a very close comparison with retinal lesions in animal models (5). Fourth, there is indirect evidence that the rod contributions to cortical activity are very similar to those of the cones, allowing for comparisons of changes in the properties of the cortical neurons overlapping the scotomas arising from either scotopic conditions or direct retinal lesions (6,7,13,14). Fifth, the rod scotoma is completely reversible on return to photopic conditions, allowing for the measurement of ectopic cortical responses caused by short-term cortical adaptation without contamination from long-term reorganization, such as that seen in the relatively permanent developmental foveal scotomas of rod monochromats (7).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It remains unclear as to what stage of development rescue would need to be instituted in order to result in improved vision in humans, as rod monochromacy has been shown to result in alterations to inner retinal structure, 67 alterations in the photoreceptor mosaic, 68 and in reorganisation of the visual cortex. 69 It is likely that these changes alone would have an impact on visual function: even if successful targeting of cone photoreceptors with wild-type achromatopsia genes can be achieved via viral vectors, vision is unlikely to be returned to normal once such changes have occurred. A more recent study by Mancuso et al 70 has investigated the amelioration of red-green colour vision deficiency in an animal model of protanopia.…”
Section: Practical Limitations Of Colour Vision Deficiencymentioning
confidence: 99%